Criteria for developing communication skills of internal affairs officers in their relations with the public (Zien Journal of Social Sciences and Humanities, 2026)
Another characteristic feature of the professional activity of internal affairs officers in ensuring the stability of society is their ability to interact with a wide range of environments. The activity of ensuring a culture of communication is of great importance in the professional competence of an internal affairs officer.